Aleocharine rove beetles (Coleoptera, Staphylinidae) associated with Leptogenys Roger, 1861 (Hymenoptera, Formicidae) I. review of three genera associated with L. distinguenda (Emery, 1887) and L. mutabilis (Smith, 1861) - Hashim, Rosli; von Beeren, C.; Maruyama, M. (2010)
Three myrmecophilous genera of Aleocharinae (Staphylinidae) associated with Leptogenys distinguenda (Emery, 1887) and L. mutabilis (Smith, 1861) are reviewed with descriptions of new taxa: Maschwitzia Kistner, 1989, Togpelenys Kistner, 1989 and Witteia Maruyama & von Beeren, gen. n. (type species: Witteia dentilabrum Maruyama & von Beeren, sp. n.). The following new combinations are proposed: Zyras (s. lat.) aenictophila (Kistner, 1997), comb. n. (ex Maschwitzia), Zyras (s. lat.) dichthadiaphila (Kistner in Kistner et al., 2003), comb. n. (ex Maschwitzia), Maschwitzia derougemonti (Pace, 1984), comb. n. (ex Wroughtonilla Wasmann, 1899), Maschwitzia watanabei (Maruyama, 2004), comb. n. (ex Wroughtonilla), Maschwitzia dilatata (Pace, 2005), comb. n. (ex Wroughtonilla), Witteia borneensis (Pace, 1986), comb. n. (ex Wroughtonilla). These genera belong to the Wroughtonilla genus group of the tribe Lomechusini.